Longitudinal Physical Development of Future Professional Male Soccer Players: Implications for Talent Identification and Development? - Saward, Chris; Hulse, Mark; Morris, John G.; Goto, Heita; Sunderland, Caroline; Nevill, Mary E. (Frontiers in Sports and Active Living, 2020)
The present study examined if elite youth male association football (soccer) players aged 8–19 y (n = 2,875) from the English talent development system, who ultimately achieved professional status differed in stature, body mass, and physical performance (20-m sprint speed, slalom agility speed, vertical counter-movement jump with arm swing jump height, multistage fitness test distance) compared with their non-professional peers. The study also examined the longitudinal pattern of development of stature, body mass, and physical performance, and if this was different between future professionals and non-professionals, while considering the effects of playing position. Multilevel modeling of the 8,898 individual (player-occasion) data points suggested that from age 12.0, the future professionals performed better in a vertical counter-movement jump with arm swing test and slalom agility test than future non-professionals, and improved at a faster rate, so that by age 18.0 the differences in vertical counter-movement jump with arm swing and slalom agility performance were 1.7 cm (p < 0.001, d = 0.3) and 0.14 s (p < 0.001, d = 0.5), respectively. In addition, future professionals were faster (by 0.02–0.04 s on the 20-m sprint, p < 0.001, d = 0.2) and ran further in the multistage fitness test (by 47 m, p = 0.014, d = 0.2) than future non-professionals throughout their development, but there were no differences in stature or body mass during development between the groups. Whereas, multistage fitness test performance improved linearly with age, the development of all other physical characteristics was non-linear. There were inter-individual differences in the development of all characteristics, and there were differences between playing positions in the development of all characteristics. Thus, in summary, future professionals jump higher, are more agile, faster, and more endurance fit than future non-professionals as they age, and the pattern of development is different in professionals and non-professionals for vertical jumping and slalom agility performance.